In vitro and in vivo assessment of biomedical Mg–Ca alloys for bone implant applications. Issue 3 (July 2018) - Makkar, Preeti; Sarkar, Swapan Kumar; Padalhin, Andrew R.; Moon, Byoung-Gi; Lee, Young Seon; Lee, Byong Taek
Background: Magnesium (Mg)-based alloys are considered to be promising materials for implant application due to their excellent biocompatibility, biodegradability, and mechanical properties close to bone. However, low corrosion resistance and fast degradation are limiting their application. Mg–Ca alloys have huge potential owing to a similar density to bone, good corrosion resistance, and as Mg is essential for Ca incorporation into bone. The objective of the present work is to determine the in vitro degradation and in vivo performance of binary Mg– x Ca alloy ( x = 0.5 or 5.0 wt%) to assess its usability for degradable implant applications. Methods: Microstructural evolutions for Mg– x Ca alloys were characterized by optical, SEM, EDX, and XRD. In vitro degradation tests were conducted via immersion test in phosphate buffer saline solution. In vivo performance in terms of interface, biocompatibility, and biodegradability of Mg– x Ca alloys was examined by implanting samples into rabbit femoral condyle for 2 and 4 weeks. Results: Microstructural results showed the enhancement in intermetallic Mg2 Ca phase with increase in Ca content. Immersion tests revealed that the dissolution rate varies linearly, with Ca content exhibiting more hydrogen gas evolution, increased pH, and higher degradation for Mg–5.0Ca alloy. In vivo studies showed good biocompatibility with enhanced bone formation for Mg–0.5Ca after 4 weeks of implantation compared with Mg–5.0Ca alloy. Higher initial corrosion rate with prolonged inflammation and rapid degradation was noticed in Mg–5.0Ca compared with Mg–0.5Ca alloy. Conclusions: The results suggest that Mg–0.5Ca alloy could be used as a temporary biodegradable implant material for clinical applications owing to its controlled in vivo degradation, reduced inflammation, and high bone-formation capability.